Numerical modeling of the behavior of concrete exposed to chloride ions by coupling age and mechanical stresses - Roubila Bendjaiche; Hocine Boudjehm; Zahreddine Nafa; fathe bouteldja (The Journal of Engineering and Exact Sciences)
This study proposes a quantitative examination of the issue of chloride ion infiltration in concrete under mechanical strain in a hostile setting while considering the influence of time, commonly referred to as the aging effect. The relationship between the diffusion coefficient and age, when subjected to specific levels of uniaxial or biaxial stresses for various W/C ratios, has allowed us to assess the concentration of chloride ions and the time needed for corrosion to begin through the coating layer in three dimensions. The numerical model results corroborate the notion that the corrosion process is affected by the fluctuation of the diffusion coefficient, which is directly linked to the age factor and the mechanical stresses exerted on the concrete. The model also emphasizes the extended distribution of chloride ion concentration at a certain depth, which is connected to the ratio of water to cement, influenced by the diffusion coefficient and the degree of mechanical stress in older structures.